Improving Students Reading Comprehension Through Round Robin Technique on Narrative Text - Hukunala, Gresye Kristina (English Language Education Study Program, 2023)
This research aims to respond to students problems in reading comprehension. In this research, the researcher used round robin technique to teach students reading comprehension of narrative text. Round robin is a technique that gives students opportunities to encourage student ideas in a group. The researcher conducted classroom action research consisting of planning, acting, observing, and reflecting. The participant in this research were eight- grade students which consisted of 28 students of SMPN 5 Salatiga.This research was conducted in 2 cycles. Research data were collected using observation checklists, field notes, and tests. The result of the observation and field note showed an increase in students who looked enthusiastic and showed good attitudes in teaching learning process. The result of the test showed the main score of cycle 1 was 62.72 and cycle 2 was 78.21. The improvement 10.61.